Performance and Comparison of Energy Efficient MAC Protocol in Wireless Sensor Network (International Journal of Engineering and Computer Science, 2017)
Energy efficiency is the kernel issue in the designing of wireless sensor network (WSN) MAC protocols. Energy efficiency is a major consideration while designing wireless sensor network nodes. Most sensor network applications require energy autonomy for the complete lifetime of the node, which may span up to several years. These energy constraints require that the system be built such that Wireless sensor networks use battery-operated computing and sensing devices. A network of these devices will collaborate for a common application such as environmental monitoring. Each component consumes minimum possible power, ensure the average successful transmission rate, decrease the data packet average waiting time, and reduce the average energy consumption. Influencing by the design principles of traditional layered protocol stack, current MAC protocol designing for wireless sensor networks (WSN) seldom takes load balance into consideration, which greatly restricts WSN lifetime. This paper proposes a new MAC protocol called Energy-Efficient MAC (E2MAC) focuses mainly on achieving good performance in packet delay and packet delivery rate while being operated on very low level of energy consumption. E2MAC is designed based on a previously defined MAC protocol called S-MAC & T-MAC with the addition of adaptive wakeup time and next awake node first packet scheduling features. We compare the performance of S-MAC & T-MAC with E2MAC. The results show that E2MAC exhibits superior performance particularly in dense/high load networks.